2013
DOI: 10.1158/1078-0432.ccr-12-3764
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Chemotherapeutic Treatment on Learning in Adolescent Mice: Implications for Cognitive Impairment and Remediation in Childhood Cancer Survivors

Abstract: Purpose Among children diagnosed with acute lymphoblastic leukemia (ALL) and given chemotherapy-only treatment, 40-70% of survivors experience neurocognitive impairment. The present study used a preclinical mouse model to investigate the effects of early exposure to common ALL chemotherapeutics methotrexate (MTX) and cytarabine (Ara-C) on learning and memory. Experimental Design Pre-weanling mouse pups were treated on postnatal day (PND) 14, 15, and 16 with saline, MTX, Ara-C, or a combination of MTX and Ara… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The operant responding task is an example of instrumental/reinforcement learning and involves frontal cortical and many subcortical brain regions, including the hippocampus, ventral tegmental area, nucleus accumbens, and amygdala (Cardinal, Parkinson et al 2002; Bisen-Hersh, Hineline et al 2013). These brain regions were not primary sites of damage induced by the stroke, as seen by their ability to take up the TTC staining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The operant responding task is an example of instrumental/reinforcement learning and involves frontal cortical and many subcortical brain regions, including the hippocampus, ventral tegmental area, nucleus accumbens, and amygdala (Cardinal, Parkinson et al 2002; Bisen-Hersh, Hineline et al 2013). These brain regions were not primary sites of damage induced by the stroke, as seen by their ability to take up the TTC staining.…”
Section: Discussionmentioning
confidence: 99%
“…All behavioral testing was done by an experimenter blinded to the treatment of the individual animals. The novel object recognition task was executed as described previously by our laboratory (Bisen-Hersh et al 2013). On the morning of day 6, mice were individually placed into the testing cage for a 20-min acclimation period and then returned to their home cage for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that the mice that had received MTX alone or MTX in conjunction with AraC performed less well on behavioral tasks when compared to the non-treatment cohort. 20 Unfortunately, the study did not investigate physiological changes that could have confirmed the behavioral results, such as molecular assays. Assessment of neurophysiology could be beneficial in understanding mechanistic changes that lead to damage.…”
Section: Introductionmentioning
confidence: 99%
“…Instrumental discrimination learning was assessed in mice using an appetitive‐motivated operant conditional discrimination procedure (Bisen‐Hersh et al, ) that used a tone/light compound stimulus and temporal duration. Following the habituation period, mice were separated into individual cages, weighed and food‐restricted for 24 h prior to the start of experimental testing.…”
Section: Methodsmentioning
confidence: 99%